Ansiedade, depressão e engagement no trabalho em aprimorandos e aperfeiçoandos da Faculdade de Medicina de São José do Rio Preto/SP - Gonsalez, Elizangela Gianini (2016)
Introduction: residency programs, multidisciplinary residency and professional development are teaching modalities characterized by in-service training under the supervision of qualified professionals seeking to develop skills and competencies by newly graduates in different specialties. The work process in-service training programs are seen as stressful, producing physical and emotional disorders that compromise the quality of life, well-being and professional satisfaction and consequently damage the health care quality of users' health services. Psychological disorders such as anxiety and depression may arise between professional training in residency programs and professional development. Objectives: To assess levels of anxiety, depression and engagement of professionals enrolled in the Enhancement Programs and Professional Improvement in Health of a higher education institution in the state of São Paulo. Methods: This is a descriptive cross-sectional study, a population-based conducted among professionals enrolled in the Enhancement Programs and Professional Improvement in Health Data were collected between the months of November 2013 to February 2014, using instruments: one prepared by the authors, to collect the Sociodemographic data, the Beck Anxiety Scale (BAI), Beck Depression Scale (BDI-II) and the Utrecht Work Engagement Scale (UWES) consists of 17 questions divided in force size, dedication and absorption. Results: The study included 82 professionals from different professional areas, 31 aprimorandos and 51 aperfeiçoandos; 85.4% were female; the age range was 22-32 years old, with a median of 25 years; 90.2% single, 59.8% were satisfied with the work and 61.0% thought about quitting the program. The levels of anxiety and depression among professionals have been 46.8%. There was an association between levels of anxiety and depression (p = 0.001). The levels of engagement were very high in the force size, high dedication dimension and overall score, and medium in size absorption (71.61%, 58.03%, 53.75% and 51.22% of the professionals, respectively). Conclusion: The levels of anxiety and depression found are significant and evidence the presence of discouraging factors and/or stressful related to the training process in the programs evaluated. However, these professionals were closely related work, are responsible, motivated and dedicated to work and patients. It is stressed, however, that knowledge about the reality of professionals enrolled in improvement and professional development programs in health is critical to the analysis and intervention on the negative factors and strengthen the positive aspects of the environment / training process, ensuring further development of the professional.